2019
DOI: 10.3389/fimmu.2019.02519
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-11 Mediates Neutrophil Chemotaxis and Extracellular Trap Formation During Acute Gouty Arthritis Through Alteration of Cofilin Phosphorylation

Abstract: Gout is characterized by attacks of arthritis with hyperuricemia and monosodium urate (MSU) crystal-induced inflammation within joints. Innate immune responses are the primary drivers for tissue destruction and inflammation in gout. MSU crystals engage the Nlrp3 inflammasome, leading to the activation of caspase-1 and production of IL-1β and IL-18 within gout-affected joints, promoting the influx of neutrophils and monocytes. Here, we show that caspase-11−/− mice and their derived macrophages produce significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 90 publications
4
50
0
Order By: Relevance
“…Knockdown of caspase‐5 reduces IL‐1α release and cytokines associated with SASP such as IL‐6, MCP1, and IL‐8, suggesting that caspase‐5 is required for IL‐1α release during senescence in vitro. We also showed that IL‐6, KC, and TNF‐α are drastically reduced in the absence of caspase‐11 33 . Additionally, caspase‐11 −/− mice showed reduction in the level of IL‐1α and KC in response to MRSA infection 60 .…”
Section: Il‐1α Is a Direct Substrate Of Mouse Caspase‐11 And Human Camentioning
confidence: 53%
See 4 more Smart Citations
“…Knockdown of caspase‐5 reduces IL‐1α release and cytokines associated with SASP such as IL‐6, MCP1, and IL‐8, suggesting that caspase‐5 is required for IL‐1α release during senescence in vitro. We also showed that IL‐6, KC, and TNF‐α are drastically reduced in the absence of caspase‐11 33 . Additionally, caspase‐11 −/− mice showed reduction in the level of IL‐1α and KC in response to MRSA infection 60 .…”
Section: Il‐1α Is a Direct Substrate Of Mouse Caspase‐11 And Human Camentioning
confidence: 53%
“…Recent study showed that at sublytic levels of inflammasome activation, and in the absence of pyroptotic cell death, gasdermin D pores mediate the release of IL‐1β or IL‐18 and other cytosolic proteins 84 . Notably, we have shown that the release of IL‐1β from macrophages in response to MSU was not accompanied by cell death 33 . Our findings are corroborated by recent reports describing how gasdermin forms pores within the intact plasma membrane, allowing the release of IL‐1β independently of cell death 85,86 .…”
Section: Non‐apoptotic Functions Of Caspase‐11 and Gasdermin Dmentioning
confidence: 62%
See 3 more Smart Citations